2015
DOI: 10.5430/jnep.v5n4p108
|View full text |Cite
|
Sign up to set email alerts
|

Making the case for differentiation of registered nurse practice: Historical perspectives meet contemporary efforts

Abstract: In recent years, the nursing profession in the United States (U.S.) has made new efforts to advance the education of registered nurses (RNs) who provide direct patient care to the baccalaureate degree in nursing (BSN). This renewed focus is partially due to current research noting that an RN's education is positively correlated with improved patient outcomes. In spite of the research and efforts, multiple educational pathways for entry into RN practice continue to thrive throughout the U.S. and around the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…There are a few limitations to the present study that should be considered when interpreting the results. First, the findings are only applicable to nursing practice in Dutch hospitals, although similar findings on differentiated nursing practice in the United States were described by Matthias ( 2015 ). Despite this, the present findings may help to predict trends in nursing practice transitions in other countries.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There are a few limitations to the present study that should be considered when interpreting the results. First, the findings are only applicable to nursing practice in Dutch hospitals, although similar findings on differentiated nursing practice in the United States were described by Matthias ( 2015 ). Despite this, the present findings may help to predict trends in nursing practice transitions in other countries.…”
Section: Discussionsupporting
confidence: 58%
“…States were described by Matthias (2015). Despite this, the present findings may help to predict trends in nursing practice transitions in other countries.…”
Section: Study Limitationsmentioning
confidence: 72%
“…Conversely, the present study results do not confirm previous studies and showed no statistically significant association between educational attainment and knowledge of the GCS (Al-Quraan & AbuRuz, 2016; Jadduoa, Mohammed & Abbas, 2013). According to Matthias (2015), nurses with postgraduate degrees are not shown to be more accurate in assessment compared with registered nurses who possess either a diploma or a bachelor's degree. This research gap regarding the complexity of nurses' educational attainment warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Diploma Programs, established in the 1870s, were the first pathway to nursing (Matthias, 2015). Diploma programs were typically either affiliated with hospitals or were independent in an apprenticeship model to provide education and career options for women (Anderson, 1981;Petges & Sabio, 2020).…”
Section: Differentiated Educational Pathways In Nursingmentioning
confidence: 99%